VD_FINDINFO HC / 2016 / 48 vom 21. Dezember 2015 - VD Tribunal cantonal (2015)
BAIL À LOYER, LOCAL PROFESSIONNEL, SOLIDARITÉ PASSIVE, CAUTIONNEMENT, CAS CLAIR | 29 al. 2 Cst., 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)